Desain Perancangan Sistem Pakar Pemeriksaan Dimensi Dan Arah Pada Tanda Tangan - Andhy Permadi (FORMAT, 2023)
The signature is a fully reliable proof of identity to explain the authenticity of a document, which becomes a serious problem that the acceptance of a signature as evidence of a person's recognition, in this case, is not accompanied by its identification, this causes great danger to the possibility of forgery and various other crimes related to signatures. The lack of experts and the lack of application of knowledge about this, and the development of crimes in this field, it is necessary to overcome using investigations based on science and technology as a tool for the prevention and prosecution of crimes, especially in the field of signature examination. The design of the expert system in this study is designed to assist signature examiners in anticipating the increasing crime of signature forgery, with restrictions on the dimensions and direction of the signature.